Induction of apoptosis by ginsenoside Rk1 in SK-MEL-2-human melanoma - Kim, Ji Seong; Joo, Eun Ji; Chun, Jaemoo; Ha, Young Wan; Lee, Jue-Hee; Han, Yongmoon; Kim, Yeong Shik (PHARMACEUTICAL SOC KOREA, 2012)
Ginsenosides are active compounds isolated from Panax ginseng Meyer. Among these ginsenosides, less polar ginsenosides such as ginsenoside Rg3 and ginsenoside Rh2 have been demonstrated to have tumor inhibitory effects because of their cytotoxicity. In this study, we evaluated the apoptotic effects of ginsenoside Rk1 in SK-MEL-2 human melanoma. Ginsenoside Rk1 isolated from red ginseng is one of the novel ginsenosides that shows strong cytotoxicity compared to ginsenoside Rg3 in dose- and time-dependent manners. The results of DNA fragmentation, 4',6-diamidino-2-phenylindole staining, and flow cytometric analysis are corroborated that ginsenoside Rk1 induced apoptosis in SK-MEL-2 cells. Western blot analysis revealed up-regulation of Fas, FasL, and Bax protein expression and down-regulation of procaspase-8, procaspase-3, mutant p53 and Bcl-2 protein expression. These findings suggest that ginsenoside Rk1 might be a promising compound to induce apoptosis through both extrinsic and intrinsic pathways in SK-MEL-2 cells.